Prolonged High Fat Diet Worsens the Cellular Response to a Small, Covert-like Ischemic Stroke. (15th May 2019) - Fifield, Kathleen E.; Rowe, Todd M.; Raman-Nair, Joanna B.; Hirasawa, Michiru; Vanderluit, Jacqueline L.
Abstract: Obesity is associated with worse neurological outcomes following overt ischemic strokes. The majority of strokes however, are covert, small strokes that often evade detection. How obesity impacts the cellular response to covert strokes is unclear. Here, we used a diet-induced obesity model by feeding mice a high fat diet (HFD) and examining its impact on the behavioral and cellular responses to either an Endothelin-1-induced focal ischemic stroke or a saline injection (control). Specifically, we examined cells in regions with different levels of blood perfusion: the non-perfused core, the hypo-perfused surround and the perfused region around the infarct. We show that HFD selectively exacerbated the response to stroke but not to saline injections. Stroke affected the composition of microglia/macrophages, astrocytes and neurons within each region of perfusion. In the non-perfused core, the majority of cells were Iba-1 + microglia and macrophages. HFD resulted in a greater infiltration of CD68 + macrophages into the infarct core while CD68 + /TMEM119 + microglia were reduced. Furthermore, there was a trend towards an increased spread of the astrogliosis scar from the infarct border in the HFD condition. Within the hypo-perfused region, significantly fewer neurons survived in HFD-fed mice than Chow-fed mice, suggesting that neurons in the HFD condition have an increased vulnerability. In summary, diet-induced obesity exacerbates covert-like stroke injuries by worsening the cellular responses in the varying levels of perfusion across the infarct. Highlights: Prolonged high fat diet worsens the effects of a small covert-like ischemic stroke. Prolonged high fat diet increased the stroke-induced infarct size. Prolonged high fat diet amplified the infiltration of macrophages into the ischemic core. Prolonged high fat increased the susceptibility of neurons to ischemic injury.